The Influence of Corporate Social Responsibility and Environmental Management Accounting on the Sustainability Performance of the Patra Bali Resort and Villas - ARIENATA, Ketut Yoga Widiyasa; SAPUTRA, Komang Adi Kurniawan; MANUABA, I. B. Made Putra (Journal of Tourism Economics and Policy, 2024)
This research aims to examine and analyze the impact of Corporate Social Responsibility and Environmental Management Accounting on Sustainability Performance. Conducted by The Patra Bali Resort & Villas, the study includes 79 respondents selected through saturation sampling. All data obtained from the questionnaire distribution are deemed suitable and further analyzed using multiple linear regression, hypothesis testing (t-test and F-test). The results indicate that (1) Corporate Social Responsibility significantly and positively influences Sustainability Performance at The Patra Bali Resort & Villas. This suggests that an increase in Corporate Social Responsibility leads to an improvement in Sustainability Performance at The Patra Bali Resort & Villas. (2) Environmental Management Accounting significantly and positively affects Sustainability Performance at The Patra Bali Resort & Villas. This implies that better or increased Environmental Management Accounting results in an improved Sustainability Performance at The Patra Bali Resort & Villas.